The relationship between self-esteem, optimism, and resilience among undergraduates in Malaysia. - Archanaa, Muthiah; Beh, Jin Xuan; Kayathri, Krishnamurthi (2022)
Students’ adaptability to university life is considered a growing physical and psychological distress that undergraduate students experience. Resilience has grown more common among ng undergraduates; hence, several psychological elements were viewed as a stage of development that may influence a person’s academic transition. The present study investigated the relationship between self-esteem and optimism as predictors of resilience among Malaysian undergraduates by implementing the resilience theory. A quantitative cross-sectional study was conducted online among Malaysian undergraduates aged between 19 to 25 years old. A total of 153 participants were recruited for the present study via the convenience sampling method. After all, only 59 participants were used for the data analysis according to the calculated sample size. Online questionnaires were distributed across various social media platforms, which include Facebook, Microsoft Teams, E-mail, and WhatsApp. The variables of this study were measured by using Rosenberg Self-Esteem Scale (RSES), Revised Life Orientation Test (LOTR), and Brief Resilience Scale (BRS). The findings revealed that self-esteem and optimism were significant and positively predicted resilience among undergraduates in Malaysia by using Multiple Linear Regression. In conclusion, present study may provide a greater understanding of relevant topics as well as essential references and suggestions for future researchers. Legal authorities could be able to use the insights to adopt new measures that can assist students in improving their resilience in the future.